BRCA carriers, prophylactic salpingo-oophorectomy and menopause: clinical management considerations and recommendations. (September 2012) - Finch, Amy; Evans, Gareth; Narod, Steven A
Women who inherit a mutation in either the BRCA1 or BRCA2 gene have greatly elevated lifetime risks of ovarian cancer, fallopian tube cancer and breast cancer. Preventive surgical removal of the ovaries and fallopian tubes (salpingo-oophorectomy) is recommended to these women, often prior to natural menopause, to prevent cancer. The ensuing hormone deprivation may impact on health and quality of life. Most of these women experience menopausal symptoms shortly after surgery; however, there may also be longer term consequences that are less well understood. In this review, we highlight recent studies that examine the implications of salpingo-oophorectomy on health and quality of life in BRCA -positive women and we discuss the care of women following prophylactic surgery.